Contact lens with electromagnetic shielding function and preparation method thereof
By designing three-layer contact lenses, the electromagnetic shielding mechanism of reflection-absorbing-reflection-reabsorbing-reabsorbing-reabsorbing-reabsorbing-reabsorbing-reabsorbing-reabsorbing-reabsorbing-reabsorbing-reabsorbing-reabsorbing-reabsorbing-reabsorbing-reabsorbing-reabsorbing-reabsorbing-reabsorbing-reabsorbing-expected-reabsorbing-expected-reabsorbing-expected-reabsorbing-expected-reabsorbing-expected-reabsorbing-expected-reabsorbing-expected-reabsorbing-expected-reabsorbing-expected-expected-reabsorbing-expected-expected-reabsorbing-expected-expected-reabsorbing-expected-expected-reabsorbing-expected-expected-expected-reabsorbing-expected-expected-expected-reabsorbing-expected-expected-expected-expected-reabsorbing-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-expected-
Patent Information
- Application Number
- CN202411796468.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
AI Technical Summary
When existing contact lenses are exposed to electromagnetic waves for a long time, it is difficult to effectively shield electromagnetic waves, resulting in low-temperature burns or dehydration in the eyes, and it is difficult to take into account both light transmittance and shielding performance.
A three-layer structure contact lens is designed, including a linear reflective layer, a porous absorbing layer and a sheet reflective layer. The linear reflective layer uses one-dimensional metal nanowire conductive hydrogel, the porous absorbing layer uses magnetic composite ink, and the sheet reflective layer uses Mxene material, which realizes electromagnetic shielding through the reflection-absorbing-reflection-reabsorbing mechanism.
While ensuring transmittance, the electromagnetic shielding efficiency is significantly improved, the eyes are protected from the harm of electromagnetic waves. At the same time, the process is convenient for mass production and the materials are biocompatible.
Smart Images

Figure CN119717306A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of contact lenses, and in particular to a contact lens with electromagnetic shielding and a preparation method thereof. Background Art
[0002] With the rapid development of electronic devices and information technology, our eyes are increasingly exposed to various electromagnetic waves. In particular, the popularity of contact lens-type wearable devices, such as those used to diagnose glaucoma or diabetes, which use electromagnetic waves for radio frequency technology, further increases the chances of eyes being exposed to electromagnetic waves. Long-term exposure to electromagnetic waves, even at relatively weak levels of electromagnetic interference (EMI), can cause low-temperature burns or dehydration in the eyes. This is because the eyes are very sensitive to continuous exposure to electromagnetic waves. In addition, with the development of Internet of Things (IoT) technology, the level of electromagnetic waves in the environment is also steadily increasing, which further exacerbates the threat to eye health. Therefore, it has become particularly important to shield electromagnetic waves from entering the eyes. However, since anti-electromagnetic radiation contact lenses need to take into account both transmittance and shielding effectiveness, and these two cannot be taken into account at the same time, it is necessary to develop a reasonable and effective electromagnetic shielding structure based on contact lens devices. Summary of the invention
[0003] The purpose of the present invention is to provide a contact lens with electromagnetic shielding and a preparation method thereof.
[0004] The electromagnetic shielding contact lens of the present invention comprises a linear reflection layer, a porous absorption layer, and a sheet reflection layer arranged from the inside to the outside; the inside refers to the eye side;
[0005] The porous absorption layer is an annular structure, the inner diameter of which is larger than the pupil diameter; the pupil area is exposed to ensure the normal passage of the light path;
[0006] The porous absorption layer is used to absorb electromagnetic waves, and the sheet-like reflection layer is used to reflect electromagnetic waves and achieve high transparency.
[0007] The linear reflection layer is used to reflect the electromagnetic waves transmitted from the porous absorption layer to the surface of the linear reflection layer back to the porous absorption layer, and reabsorb the reflected electromagnetic waves in the porous absorption layer, thereby forming an electromagnetic wave shielding mechanism of reflection-absorption-re-reflection-reabsorption on the surface of the linear reflection layer and in the porous absorption layer.
[0008] Furthermore, the linear reflective layer is a mixture of one-dimensional metal nanowires and contact lens raw materials, and a conductive network is formed by interconnecting the one-dimensional nanowires;
[0009] The one-dimensional metal nanowire is at least one of silver nanowire, copper nanowire, gold nanowire and nickel nanowire aqueous dispersion, the diameter of the nanowire is 30-60nm and the length is 20-120um. The contact lens raw material is a hydrogel material, specifically at least one of HEMA, silicone hydrogel, PMMA and RGP.
[0010] Furthermore, the sheet-like reflective layer is made of Mxene material, and the structure is encapsulated and reflective shielding is provided by spraying the Mxene material;
[0011] The porous absorption layer is made of magnetic composite ink material; the magnetic composite ink is a mixture of synthetic resin, resin curing agent, ferromagnetic filler and sodium chloride crystal particles; the resin curing agent used is a curing agent, which is a substance for adjusting the fluidity and viscosity of the ink.
[0012] The outer ring radius of the porous absorption layer is 7 mm, and the inner ring diameter is 2.5 mm.
[0013] Based on the contact lens with electromagnetic shielding of the present invention, a method for preparing the contact lens is also proposed, comprising the following steps:
[0014] Step 1: Preparation of magnetic composite ink and conductive hydrogel
[0015] According to the weight percentage, 20-34 parts of synthetic resin, 10-17 parts of resin curing agent, 49-60 parts of ferromagnetic filler, and 10-15 parts of sodium chloride crystals are weighed, stirred evenly and degassed to prepare a magnetic composite ink;
[0016] Weigh 30-50 parts of metal nanowire dispersion and 50-70 parts of contact lens raw materials, stir to form a uniform conductive hydrogel;
[0017] Step 2: Preparation of linear reflective layer and porous absorption layer
[0018] The magnetic composite ink is transferred to the contact lens concave mold through a circular transfer template, and initially dried and formed to form a magnetic composite ink layer;
[0019] The conductive hydrogel is dripped into the concave mold of the glasses, covered with a convex mold, and then dried to form a linear reflective layer on the surface of the magnetic composite ink layer;
[0020] After demoulding, the magnetic composite ink layer is placed in water, and the sodium chloride crystals in the magnetic composite ink layer are dissolved in water to form a porous structure. The porous magnetic composite ink layer is the porous absorption layer.
[0021] Step 3: Prepare a flaky reflective layer
[0022] The linear reflective layer and the porous absorption layer are placed on a mold with the same curvature, and the Mxene package is sprayed on the side of the porous absorption layer to form a sheet-like reflective layer.
[0023] Furthermore, the synthetic resin is at least one of alkyd resin, polyurethane, epoxy resin, vinyl chloride-acetic acid copolymer, polyethylene ethyl ether, nitrocellulose, polyurethane resin, and bisphenol A epoxy resin; the ferromagnetic filler is at least one of magnetizable iron oxide, ferroferric oxide, and ferric oxide powder;
[0024] Furthermore, in step 1, specifically: weigh 25 parts of synthetic resin, 10 parts of resin curing agent, 50 parts of ferromagnetic filler, and 15 parts of sodium chloride crystals by weight, stir evenly and degas, to obtain a magnetic composite ink.
[0025] Furthermore, in step 1, specifically: weigh 30 parts of metal nanowire dispersion and 70 parts of contact lens raw materials, stir and form a uniform conductive hydrogel.
[0026] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
[0027] The contact lens with electromagnetic shielding proposed by the present invention is designed with a three-layer structure, using a one-dimensional metal nanowire conductive hydrogel as a linear reflective layer, preparing a porous absorption layer, and finally spraying Mxene as a sheet reflective layer for encapsulation. When external electromagnetic waves enter the human eye, due to the impedance mismatch of the sheet reflective layer, a part of the electromagnetic waves will be reflected first, and the remaining electromagnetic waves will enter the material. The porous absorption layer uses magnetic materials, has high magnetic permeability, and has a large number of pore structures inside. The shielding of electromagnetic waves is mainly based on the absorption mechanism. Finally, the electromagnetic waves are reflected again through the linear reflective layer, and the entire structure forms a reflection-absorption-reflection-reabsorption electromagnetic shielding mechanism. The one-dimensional metal nanowire has the characteristics of high conductivity and high transparency, and can achieve a certain shielding effectiveness on the basis of ensuring transmittance. The porous absorption layer uses magnetic composite ink. Although the magnetic composite ink is black ink, the structure is made into a circular ring to avoid the optical area and will not cause a large blockage to vision. Finally, Mxene is sprayed as an encapsulation layer. The Mxene structure is a two-dimensional material. Spraying Mxene can not only increase the conductivity, but also enhance the stability of the metal nanowire. The design of this structure ensures the transmittance of the contact lens while taking into account the electromagnetic shielding effectiveness.
[0028] 1. The manufacturing process of the contact lens with electromagnetic shielding proposed in the present invention is easy to combine with the cosmetic contact lens process, has the conditions for mass production, and has the potential for future industrialization.
[0029] 2. The materials used in the electromagnetic shielding contact lenses proposed in the present invention are all biocompatible and meet the requirements of wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0031] Figure 1 It is a schematic diagram of the cross-sectional structure of the contact lens with electromagnetic shielding of the present invention;
[0032] Figure 2 It is a schematic diagram of the shielding mechanism of the contact lens with electromagnetic shielding of the present invention;
[0033] Figure 3 It is a schematic diagram of the preparation principle of the contact lens with electromagnetic shielding of the present invention;
[0034] Figure 4 is a top view schematic diagram of a porous absorption layer;
[0035] Figure 5 is a porous structure diagram inside the porous absorption layer obtained by using an electron scanning microscope;
[0036] Figure 6 The figure is a comparison chart of the electromagnetic shielding effectiveness of the contact lens of the present invention and the contact lens without a porous absorbent layer.
[0037] Among them, 1. Sheet-shaped reflective layer; 2. Linear reflective layer; 3. Porous absorption layer. DETAILED DESCRIPTION
[0038] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described in detail below in conjunction with the embodiments and drawings. It should be understood that the drawings described here are only some embodiments of the present application and are not intended to limit the present invention.
[0039] Embodiment 1
[0040] The present invention is a contact lens for electromagnetic shielding, which adopts a layered structure design, such as Figure 1 As shown, from inside to outside, there are linear reflection layer 3, porous absorption layer 2 and sheet reflection layer 1; the inside refers to the eye side. According to the electromagnetic shielding principle, if a better shielding effect is to be achieved, the shielding material is required to have excellent conductivity and magnetic permeability. Therefore, the structure proposed in the design can achieve a better shielding effect.
[0041] The porous absorption layer 2 is used to absorb electromagnetic waves, and the linear reflection layer 3 is used to reflect the electromagnetic waves transmitted from the porous absorption layer 2 to the surface of the linear reflection layer 3 back to the porous absorption layer 2, and the reflected electromagnetic waves are reabsorbed in the porous absorption layer 2. A reflection-absorption-re-reflection-re-absorption electromagnetic wave shielding mechanism is formed on the surface of the linear reflection layer 3 and the inside of the porous absorption layer 2.
[0042] like Figure 2 As shown, the contact lens of the present invention is designed into a layered structure to further enhance the electromagnetic shielding effect. When the external electromagnetic wave reaches the contact lens of the present invention, a part of the electromagnetic wave will be reflected first due to the mismatch between the outer surface layer of the contact lens and the air impedance. From the following electromagnetic wave shielding formula (1), it can be obtained that the total electromagnetic shielding effectiveness SE T Divided into reflection-based SE R and absorption-based SE A , and SE representing multiple reflections M。 From the reflection efficiency formula (2), it can be seen that the magnitude of the reflection efficiency is related to the electrical conductivity, magnetic permeability, and frequency. From the absorption efficiency formula (3), it can be seen that the magnitude of the absorption efficiency is related to the thickness, magnetic permeability, electrical conductivity, and frequency. Electromagnetic waves are absorbed by the synergistic effect of multiple loss mechanisms such as hysteresis loss, polarization loss, and ohmic loss. Considering the light transmission of the contact lens, a porous absorption layer 2 is designed that does not affect the central optical zone. Since the porous absorption layer 2 has a high magnetic permeability, it can be seen from formula (3) that the absorption efficiency of the porous absorption layer 2 is increased, and the pore structure of the porous material causes the electromagnetic wave to be continuously scattered during the propagation process, that is, the electromagnetic wave will change direction when encountering the pore interface, thereby reducing the linear propagation distance of the electromagnetic wave and increasing the attenuation of the electromagnetic wave inside the material. The pore structure inside the porous material can also absorb the energy of the electromagnetic wave. When the electromagnetic wave propagates in the pore, it will interact with the atoms and molecules on the pore wall, converting the energy of the electromagnetic wave into heat energy or other forms of energy, thereby reducing the penetration ability of the electromagnetic wave. When the remaining electromagnetic waves pass through the porous absorption layer 2, the high conductivity of the linear reflection layer 3 reflects the electromagnetic waves back to the porous absorption layer 2. Figure 2 The porous absorption layer 2 and the linear reflection layer 3 form an absorption-reflection-reabsorption electromagnetic shielding mechanism. The elliptical loop inside the porous absorption layer 2 indicates the magnetic flux lines, which produce hysteresis loss. The conductivity of the metal nanowires used in the linear reflection layer 3 is higher than that of the sheet reflection layer 1. Therefore, the screen and shielding effect of the linear reflection layer 3 accounts for a larger proportion. Therefore, the degree of absorption and reflection can be modulated by modifying the ratio of the linear reflection layer 3 and the porous absorption layer 2.
[0043] SE T =SE R +SE A +SE M (1)
[0044]
[0045] SE T Total electromagnetic shielding effectiveness, SE R Reflective shielding effectiveness, SE A Absorption Shielding Effectiveness, SE Mis multiple reflection, σ is conductivity, μ is magnetic permeability, and f is frequency.
[0046] The sheet-like reflective layer 1 is made of Mxene material, and the porous absorption layer 2 is made of magnetic composite ink.
[0047] The linear reflective layer 3 is a mixture of a conductive filler and a contact lens raw material; the conductive filler is a metal nanowire, which is interconnected by one-dimensional nanowires to form a conductive network, and the metal nanowire is a silver nanowire, a copper nanowire, a gold nanowire, or a nickel nanowire aqueous dispersion, and the diameter of the nanowire is 30-60nm and the length is 20-120um; the contact lens raw material is one or more of HEMA, silicone hydrogel, PMMA, and RGP.
[0048] like Figure 4 As shown, it is a top view of the porous absorption layer 2. The porous absorption layer 2 is a ring structure. The magnetic composite ink is transferred to the contact lens through the contact lens transfer process. The outer ring radius of the ring structure is 7 mm, and the inner ring radius is 2.5 mm.
[0049] The sheet-like reflective layer 1 is a spray-coated material Mxene that encapsulates the entire shielding structure, and is used to reflect electromagnetic waves and improve the stability of the contact lens.
[0050] The magnetic composite ink is a mixture of synthetic resin, resin curing agent, ferromagnetic filler and sodium chloride crystal grains.
[0051] Furthermore, the synthetic resin may be one or more of alkyd resin, polyurethane, epoxy resin, vinyl chloride-acetic acid copolymer, polyethylene ethyl ether, nitrocellulose, polyurethane resin, and bisphenol A epoxy resin;
[0052] The resin curing agent used is a substance that adjusts the fluidity and viscosity of the ink;
[0053] The ferromagnetic filler used is one or more of magnetizable iron oxide, ferroferric oxide, and ferric oxide powder. Needle-shaped crystals with particles smaller than 2 μm are selected, which are very easy to be evenly arranged in a magnetic field, thereby obtaining relatively high residual magnetism.
[0054] The sodium chloride crystal grains are smaller than 1 um; the thickness of the sheet-shaped reflective layer 1 is 10-20 um, and the thickness of the porous absorption layer 2 is 10-15 um.
[0055] Figure 6 Curve ① in the figure is the electromagnetic shielding effectiveness of the contact lens comprising only one linear reflective layer 3, and curve ② is the electromagnetic shielding effectiveness of the contact lens of the present invention. It can be seen that the electromagnetic shielding effect of the present invention is significantly improved.
[0056] Embodiment 2
[0057] Based on the contact lens with electromagnetic shielding in Example 1, Figure 3 As shown, the present invention provides a method for preparing a contact lens, comprising the following steps:
[0058] Step 1: Preparation of magnetic composite ink and conductive hydrogel
[0059] According to the weight percentage, 20-34 parts of synthetic resin, 10-17 parts of resin curing agent, 49-60 parts of ferromagnetic filler, and 10-15 parts of sodium chloride crystals are weighed, and the mixture is stirred and degassed for 5 minutes by a planetary mixer loaded with a ball mill to obtain a magnetic composite ink; the main component of the magnetic composite ink is ferromagnetic material to ensure the absorption performance. In order to achieve a better transfer effect of the ink, the ratio of ferromagnetic filler to synthetic resin is about (2-3): 1; the viscosity of the ink also has a great influence on the transfer, too high viscosity leads to the inability to transfer, and too low viscosity leads to the failure to form.
[0060] Weigh 30-50 parts of metal nanowire dispersion and 50-70 parts of contact lens raw materials, stir to form a uniform conductive hydrogel;
[0061] Step 2: preparing a linear reflective layer 3 and a porous absorption layer 2
[0062] Making a circular transfer template for transferring magnetic composite ink;
[0063] The magnetic composite ink is transferred to the contact lens concave mold, and is dried and formed in a natural state for about 3 hours to form a magnetic composite ink layer;
[0064] Add the conductive hydrogel dropwise into the concave mold of the glasses, cover it with a convex mold, and then put it into a drying oven, set the temperature to 90°, and keep it for 3 hours to form a linear reflective layer 3 on the surface of the magnetic composite ink layer;
[0065] After demoulding, the composite ink is placed in water for 2 hours, and the sodium chloride microcrystalline particles attached to the magnetic composite ink are slowly dissolved by wet separation under the infiltration of water, thereby promoting the formation of a porous microstructure on the surface and inside of the composite ink layer, and the porous magnetic composite ink layer is the porous absorption layer 2. Figure 5 As shown, the porous structure inside the porous absorption layer 2 is obtained using an electron scanning microscope.
[0066] Step 3: Prepare a sheet-like reflective layer 1
[0067] The linear reflective layer 3 and the porous absorbing layer 2 are placed on a mold with the same curvature, and Mxene is sprayed on the porous absorbing layer 2 at a distance of about 8-10 cm, for 5 seconds, and sprayed 5-10 times to form a sheet-like reflective layer 1.
[0068] Embodiment 3
[0069] Based on the contact lens with electromagnetic shielding in Example 1 and the method for preparing the contact lens in Example 2, the proportion of the linear reflective layer 3 is modified to balance the transmittance and electromagnetic shielding performance. In this embodiment, a method for preparing the contact lens is provided, comprising the following steps:
[0070] Step 1: Preparation of magnetic composite ink and conductive hydrogel
[0071] According to the weight percentage, 25 parts of synthetic resin, 10 parts of resin curing agent, 50 parts of ferromagnetic filler, and 15 parts of sodium chloride crystals were weighed by an electronic balance, stirred in a planetary mixer loaded with a ball mill, and degassed for 5 minutes to prepare a magnetic composite ink;
[0072] 30 parts of metal nanowire dispersion and 70 parts of contact lens raw materials were weighed separately using an electronic balance and stirred for 5 minutes to form a uniform conductive hydrogel;
[0073] Step 2: preparing porous absorption layer 2
[0074] A circular transfer template is made to complete the transfer of magnetic composite ink. The outer diameter of the circular transfer template is 7mm and the inner diameter is 2.5mm.
[0075] The magnetic composite ink is introduced into the circular mold and transferred to the contact lens mold concave mold with a transfer rubber head, and then left to stand for 3 hours for preliminary drying and forming;
[0076] Then, the conductive hydrogel is dripped into the concave mold, covered with a convex mold, and placed in a 90° drying oven for 3 hours; the glasses are demoulded and placed in water for 2 hours. Through wet separation, the sodium chloride crystals in the magnetic composite ink will dissolve in water, thereby forming a porous structure in the porous absorption layer 2;
[0077] Step 3, finally, spray Mxene on the surface of the porous absorption layer 2 side by a spray gun, at a distance of 8 cm, for 5 seconds, and spray 5 times to form a sheet-like reflective layer 1.
[0078] Embodiment 4
[0079] Based on the contact lens with electromagnetic shielding in Example 1 and the method for preparing the contact lens in Example 2, this embodiment provides a method for preparing the contact lens, comprising the following steps:
[0080] Step 1: Preparation of magnetic composite ink and conductive hydrogel
[0081] According to the weight percentage, 25 parts of synthetic resin, 10 parts of resin curing agent, 50 parts of ferromagnetic filler, and 15 parts of sodium chloride crystals were weighed by an electronic balance, stirred and degassed for 5 minutes by a planetary mixer loaded with a ball mill to form a uniform ink;
[0082] 35 parts of metal nanowire dispersion and 65 parts of contact lens raw materials were weighed separately using an electronic balance and stirred for 5 minutes to form a uniform conductive hydrogel.
[0083] Step 2: preparing a linear reflective layer 3 and a porous absorption layer 2
[0084] The magnetic composite ink was introduced into a circular mold with an outer diameter of 7 mm and an inner diameter of 2.5 mm, and transferred to the contact lens mold concave mold with a transfer rubber head, and allowed to stand for 3 hours to form a magnetic composite ink layer;
[0085] Then, the conductive hydrogel is dripped into the concave mold, covered with the convex mold, and placed in a 90° drying oven for 3 hours to form a linear reflective layer 3 on the surface of the magnetic composite ink layer;
[0086] After demoulding, the layer is placed in water for 2 hours. Through wet separation, the sodium chloride crystals of the magnetic composite ink layer will dissolve in water, thereby forming a porous structure. The porous magnetic composite ink layer is the porous absorption layer 2.
[0087] Step 3: Prepare a sheet-like reflective layer 1
[0088] The linear reflective layer 3 and the porous absorption layer 2 structure are placed on a mold with the same curvature, and Mxene is sprayed on the surface of the contact lens by a spray gun at a distance of 8 cm, a time of 5 s, and sprayed 5 times to form a sheet-like reflective layer 1.
[0089] Embodiment 5
[0090] Based on the contact lens with electromagnetic shielding in Example 1 and the method for preparing the contact lens in Example 2, this embodiment provides a method for preparing the contact lens, comprising the following steps:
[0091] Step 1: Preparation of magnetic composite ink and conductive hydrogel
[0092] According to the weight percentage, 25 parts of synthetic resin, 10 parts of resin curing agent, 50 parts of ferromagnetic filler, and 15 parts of sodium chloride crystals were weighed by an electronic balance, stirred and degassed for 5 minutes by a planetary mixer loaded with a ball mill, and a uniform magnetic composite ink was formed;
[0093] 40 parts of metal nanowire dispersion and 60 parts of contact lens raw materials were weighed separately using an electronic balance and stirred for 5 minutes to form a uniform conductive hydrogel.
[0094] Step 2: preparing a linear reflective layer 3 and a porous absorption layer 2
[0095] The magnetic composite ink was introduced into a circular mold with an outer diameter of 7 mm and an inner diameter of 2.5 mm, and transferred to the contact lens mold concave mold with a transfer rubber head, and allowed to stand for 3 hours to form a magnetic composite ink layer;
[0096] Then, the conductive hydrogel is dripped into the concave mold, covered with the convex mold, and placed in a 90° drying oven for 3 hours to form a linear reflective layer 3 on the surface of the magnetic composite ink layer;
[0097] After the glasses are demoulded, they are placed in water for 2 hours. Through wet separation, the sodium chloride crystals in the magnetic composite ink layer will dissolve in water, thereby forming a porous structure. The porous magnetic composite ink layer is the porous absorption layer 2.
[0098] Step 3: Prepare a sheet-like reflective layer 1
[0099] The linear reflective layer 3 and the porous absorption layer 2 structure are placed on a mold with the same curvature, and finally Mxene is sprayed on the surface of the contact lens by a spray gun at a distance of 8 cm, a time of 5 s, and sprayed 5 times to form a sheet-like reflective layer 1.
[0100] Embodiment 6
[0101] Based on the contact lens with electromagnetic shielding in Example 1 and the method for preparing the contact lens in Example 2, this embodiment provides a method for preparing the contact lens, comprising the following steps:
[0102] Step 1: Preparation of magnetic composite ink and conductive hydrogel
[0103] According to the weight percentage, 25 parts of synthetic resin, 10 parts of resin curing agent, 50 parts of ferromagnetic filler, and 15 parts of sodium chloride crystals were weighed by an electronic balance, stirred and degassed for 5 minutes by a planetary mixer loaded with a ball mill, and a uniform magnetic composite ink was formed;
[0104] 45 parts of metal nanowire dispersion and 55 parts of contact lens raw materials were weighed separately using an electronic balance and stirred for 5 minutes to form a uniform conductive hydrogel.
[0105] Step 2: preparing a linear reflective layer 3 and a porous absorption layer 2
[0106] The magnetic composite ink was introduced into a circular mold with an outer diameter of 7 mm and an inner diameter of 2.5 mm, and transferred to the contact lens mold concave mold with a transfer rubber head, and allowed to stand for 3 hours for preliminary drying and forming to form a magnetic composite ink layer;
[0107] Then, the conductive hydrogel is dripped into the concave mold, covered with the convex mold, and placed in a 90° drying oven for 3 hours to form a linear reflective layer 3 on the surface of the magnetic composite ink layer;
[0108] After demoulding, the magnetic composite ink is placed in water for 2 hours. Through wet separation, the sodium chloride crystals in the magnetic composite ink will dissolve in water, thereby forming a porous structure. The porous magnetic composite ink layer is the porous absorption layer 2.
[0109] Step 3: Prepare a sheet-like reflective layer 1
[0110] The integrated structure of the linear reflective layer 3 and the porous absorption layer 2 is placed on a mold with the same curvature, and finally Mxene is sprayed on the surface of the contact lens by a spray gun at a distance of 8 cm, a time of 5 s, and sprayed 5 times to form a sheet-like reflective layer 1.
[0111] Embodiment 7
[0112] Based on the contact lens with electromagnetic shielding in Example 1 and the method for preparing the contact lens in Example 2, this specific embodiment provides a method for preparing the contact lens, comprising the following steps:
[0113] Step 1: Preparation of magnetic composite ink and conductive hydrogel
[0114] According to the weight percentage, 25 parts of synthetic resin, 10 parts of resin curing agent, 50 parts of ferromagnetic filler, and 15 parts of sodium chloride crystals were weighed by an electronic balance, stirred and degassed for 5 minutes by a planetary mixer loaded with a ball mill, and a uniform magnetic composite ink was formed;
[0115] Use an electronic balance to weigh 50 parts of metal nanowire dispersion and 50 parts of contact lens raw materials respectively, stir for 5 minutes, and form a uniform conductive hydrogel.
[0116] Step 2: preparing a linear reflective layer 3 and a porous absorption layer 2
[0117] The magnetic composite ink was introduced into a circular mold with an outer diameter of 7 mm and an inner diameter of 2.5 mm, and transferred to the contact lens mold concave mold with a transfer rubber head, and allowed to stand for 3 hours to form a magnetic composite ink layer;
[0118] Then, the conductive hydrogel is dripped into the concave mold, covered with the convex mold, and placed in a 90° drying oven for 3 hours to form a linear reflective layer 3 on the surface of the magnetic composite ink layer;
[0119] After the glasses are demoulded, they are placed in water for 2 hours. Through wet separation, the sodium chloride crystals in the magnetic composite ink will dissolve in water, thereby forming a porous structure. The porous magnetic composite ink layer is the porous absorption layer 2.
[0120] Step 3: Prepare a sheet-like reflective layer 1
[0121] The linear reflective layer 3 and the porous absorption layer 2 of the integrated structure are placed on a mold with the same curvature, and finally Mxene is sprayed on the surface of the contact lens by a spray gun at a distance of 8 cm, a time of 5 s, and sprayed 5 times to form a sheet-like reflective layer 1.
[0122] The above examples are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A contact lens with electromagnetic shielding, characterized in that: It includes a linear reflection layer, a porous absorption layer, and a sheet reflection layer arranged from the inside to the outside; the inside refers to the eye side; The porous absorption layer is an annular structure, and the inner diameter of the annular structure is larger than the pupil diameter; The porous absorption layer is used for absorbing electromagnetic waves.
2. A contact lens with electromagnetic shielding according to claim 1, characterized in that: The linear reflection layer is used to reflect the electromagnetic waves transmitted from the porous absorption layer to the surface of the linear reflection layer back to the porous absorption layer, and reabsorb the reflected electromagnetic waves in the porous absorption layer, thereby forming an electromagnetic wave shielding mechanism of reflection-absorption-re-reflection-reabsorption on the surface of the linear reflection layer and in the porous absorption layer.
3. A contact lens with electromagnetic shielding according to claim 1, characterized in that: The linear reflective layer is a mixture of one-dimensional metal nanowires and contact lens raw materials; The one-dimensional metal nanowire is at least one of a silver nanowire, a copper nanowire, a gold nanowire, and a nickel nanowire aqueous dispersion; The contact lens material is a hydrogel material, specifically at least one of HEMA, silicone hydrogel, PMMA, and RGP.
4. A contact lens with electromagnetic shielding according to claim 1, characterized in that: The sheet-like reflective layer is made of Mxene material.
5. The contact lens with electromagnetic shielding according to claim 1, characterized in that: The porous absorption layer adopts magnetic composite ink material.
6. The method for preparing contact lenses according to claim 1, characterized in that: The outer ring radius of the porous absorption layer is 7 mm, and the inner ring diameter is 2.5 mm.
7. A method for preparing a contact lens as claimed in claim 1, characterized in that: The steps include: Step 1: Preparation of magnetic composite ink and conductive hydrogel According to the weight percentage, 20-34 parts of synthetic resin, 10-17 parts of resin curing agent, 49-60 parts of ferromagnetic filler, and 10-15 parts of sodium chloride crystals are weighed, stirred evenly and degassed to prepare a magnetic composite ink; Weigh 30-50 parts of metal nanowire dispersion and 50-70 parts of contact lens raw materials, stir to form a uniform conductive hydrogel; Step 2: Preparation of linear reflective layer and porous absorption layer The magnetic composite ink is transferred to the contact lens concave mold through a circular transfer template, and initially dried and formed to form a magnetic composite ink layer; The conductive hydrogel is dripped into the concave mold of the glasses, covered with a convex mold, and then dried to form a linear reflective layer on the surface of the magnetic composite ink layer; After demoulding, the material is placed in water, and the sodium chloride crystals in the magnetic composite ink layer are dissolved in water to form a porous structure. The porous magnetic composite ink layer is a porous absorption layer. Step 3: Prepare a flaky reflective layer The linear reflective layer and the porous absorption layer are placed on a mold with the same curvature, and the Mxene package is sprayed on the side of the porous absorption layer to form a sheet-like reflective layer.
8. The method for preparing a contact lens according to claim 7, characterized in that: The synthetic resin is specifically at least one of alkyd resin, polyurethane, epoxy resin, vinyl chloride-acetic acid copolymer, polyethylene ethyl ether, nitrocellulose, polyurethane resin, and bisphenol A epoxy resin; The ferromagnetic filler is at least one of magnetizable iron oxide, ferroferric oxide and ferrous oxide powder.
9. The method for preparing a contact lens according to claim 7, characterized in that: Specifically, step 1 includes: weighing 25 parts of synthetic resin, 10 parts of resin curing agent, 50 parts of ferromagnetic filler, and 15 parts of sodium chloride crystals by weight, stirring evenly and degassing to obtain a magnetic composite ink.
10. The method for preparing contact lenses according to claim 7, characterized in that: Specifically, step 1 includes weighing 30 parts of metal nanowire dispersion and 70 parts of contact lens raw materials, stirring to form a uniform conductive hydrogel.
Citation Information
Cited By
Photo-thermal controlled-slow release hydrogel corneal contact lens material as well as preparation method and application thereof
CN122127535A